2018
DOI: 10.1038/s41437-018-0090-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative mRNA and miRNA expression in European mouflon (Ovis musimon) and sheep (Ovis aries) provides novel insights into the genetic mechanisms for female reproductive success

Abstract: Prolific breeds of domestic sheep (Ovis aries) are important genetic resources due to their reproductive performance, which is characterized by multiple lambs per birth and out-of-season breeding. However, the lack of a comprehensive understanding of the genetic mechanisms underlying the important reproductive traits, particularly from the evolutionary genomics perspective, has impeded the efficient advancement of sheep breeding. Here, for the first time, by performing RNA-sequencing we built a de novo transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 86 publications
0
19
0
Order By: Relevance
“…Additionally, reproduction is an extremely complex process, and the use of RNA-seq may contribute to enhancing our understanding of sheep fecundity. By comparing the mRNA and miRNA expression patterns in European mouflon and sheep, a research (Yang et al, 2018) found several key mRNAs, such as INHBA, SPP1, and ZP2, and miRNAs, such as miR-374a and miR-9-5p, which may be responsible for the success of female sheep reproduction. Pokharel et al (2018) detected and characterized some key miRNAs and mRNAs in sheep ovary which may be responsible for sheep prolificacy.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, reproduction is an extremely complex process, and the use of RNA-seq may contribute to enhancing our understanding of sheep fecundity. By comparing the mRNA and miRNA expression patterns in European mouflon and sheep, a research (Yang et al, 2018) found several key mRNAs, such as INHBA, SPP1, and ZP2, and miRNAs, such as miR-374a and miR-9-5p, which may be responsible for the success of female sheep reproduction. Pokharel et al (2018) detected and characterized some key miRNAs and mRNAs in sheep ovary which may be responsible for sheep prolificacy.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibin is a glycoprotein hormone secreted by the gonads, which can inhibit the synthesis and secretion of FSH in the pituitary [13] . Genetic characteristics of single nucleotide mutation in this study were analyzed in the 5`-UTR and exon 1 of INHBA gene in Kazakh sheep.…”
Section: Discussionmentioning
confidence: 99%
“…Ovary granular cell is the maximum cells in follicle. The growth and proliferation of granular cells is one of the most significant sign of the development of follicle [13] . We cultured the granular cell in vitro to imitate the growth and development of follicle and the estrous condition.…”
Section: Introductionmentioning
confidence: 99%
“…In non-mammal vertebrate animals, large-scale identi cation of miRNAs and lncRNAs has been implemented in many species. MiRNAs have been shown to engage in regulating the expression of genes that play key roles in follicular development, granulose cell function, oocyte maturation, and ovary pathophysiology [14,15]. In non-mammalian animals, miRNAs also play important roles in ovary development [16].…”
Section: Introductionmentioning
confidence: 99%